Isolation and Stabilization of Dark Red Food Dye from Beta vulgaris (Biological Sciences - PJSIR, 2006)
Natural highly coloured dark red pigment was isolated from Beta vulgaris, in paste and powdered form. Total colouring matter of the concentrated colour was 1.86% and 4.5%, respectively, for the paste and powdered forms, calculated as betanine. Sodium benzoate (0.01%) was used as the stabilizer for paste, while silicon dioxide (2%) was added in addition to sodiun benzoate (0.01%) for storage of the red colour in powdered form. Other param- eters that may influence the stability of the colour, such as pH, temperature and relative humidity, were studied. Toxicity evaluation, and lead and arsenic levels were determined. The addition of stabilizers, like citric acid, ascorbic acid, EDTA and sodium chloride, were also investigated, none of which showed useful effect.